Evaluating the Lower Urinary Tract Syndrome with a Telemedicine Application: An Exploration of the Electronic Audiovisual Prostate Symptom Score - Liu, Ziyu; Guan, Zhiyuan; Lan, Hongyu; Zhao, Yan; Ye, Zhiming; Lv, Daojun; Yu, Qingfeng; Wang, Ming; Peng, Kaoqing; Fu, Nanfei; Mazzon, Giorgio; Gu, Di (Frontiers in Surgery, 2022)
Background The Visual Prostate Symptom Score (VPSS) is used for the assessment of lower urinary tract symptoms (LUTS). It is usually administered by general practitioners (GPs), but in these cases, outcomes do not seem to be reflecting the real conditions of a patient well, with consequent risks of misestimations and misinterpretations. We developed an electronic audiovisual version of VPSS (EPSS), a new symptom scale based on a telemedicine mobile light-based app. The aim of this study is to test and evaluate its reliability. Methods We enrolled male patients aged between 50 and 80 years across 24 community-based healthcare facilities in Guangzhou, China. Patients were asked to complete the Chinese version of VPSS and EPSS before consultation with the urology specialists. Patients were divided into two groups based on age. First, we analyzed the rate of full understanding of EPSS using a chi-square test. Then, we analyzed the difference between each score of EPSS, VPSS, and outcomes measured by specialists, used as the reference score (RS). Finally, the outcomes were analyzed with the Spearman test and Bartlett test separately. Results Seventy-nine male patients were included (mean age 70.42 years). Patients were divided into two groups: group 1 (>70 years, n = 40) and group 2 (<70 years, n = 39). The full-understanding rates in groups 1 and 2 were 50% and 64.1%, respectively. No significant differences were noted between groups (p = 0.206). A t-test was presented between each question of VPSS, EPSS, and RS. All questions did not display significant differences (p > 0.05); total scores from the three scales had no significant differences in the evaluation of LUTS. We further explored the variations of choices made by patients in different scales. Spearman’s test among VPSS, EPSS, and RS showed positive correlations, and coefficients of the total score were 0.92, 0.91, and 0.93 (p < 0.05). Conclusion EPSS can be easily used in a significant number of patients and showed correlation with the VPSS and RS. Moreover, certain items resulted in better performance than VPSS. The results showed that EPSS could be a valuable option for both patients and GPs monitoring LUTS and particularly helpful when teleconsultations are considered, especially during the COVID-19 pandemic.